Epidernal characters of pterocactus (Opuntioideae, Cactaceae) - Faigon, A. (2011)
Stem epidermis of eight Pterocactus species was examined under light microscopy (LM) and scanning electron microscopy (SEM). The stomata belong to the paracytic type, with two to five subsidiary cells. The size of stomata and papillae and the density of both were measured and counted under LM. Under SEM the micromorphology of papillae was studied. These characters were used to distinguish anatomically the species of Pterocactus.